CONVERGING DOCTRINES, DIVERGENT RITUALS: EXPLORING BUDDHIST FUNERAL PRACTICES IN CONTEMPORARY ASIA - Bustomi, Yazid Imam; Ramadhan, Hassin Dzikry (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
Funerals are one of the activities associated with and embedded in religious practices. In the three major sects of Buddhism, there are several different practices in burying the body, even though they refer to a single teaching or concept of death. This is interesting to discuss, considering that most religions worldwide use the same practice. This study explores how funeral practices are in the Buddhist tradition and what underlies these differences. Qualitative methods are adopted to answer these questions with a literature study approach. As a result, each Buddhist sect shows its uniqueness through reflection on Buddhism in general, which is not fixed on just one rigid teaching. For instance, the Sky funeral within the Vajrayāna tradition provides a perspective that humans are bound to nature. Giving bodies to birds and other animals signifies the strength of their bond. The practice of cremation in Theravāda is a way to release the physical remains left behind in the world. With this method, they can easily continue their next spiritual journey. At the same time, Mahayāna Buddhism describes a flexible perspective on religion and funeral practices. This study also suggests a more specific approach to looking at the complexity of funerals in Buddhism, especially in areas where Buddhism is a minority, such as Indonesia.